2009
DOI: 10.1152/ajpendo.00054.2009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise and low-fat diet on adipose tissue inflammation and metabolic complications in obese mice

Abstract: Exercise training (EX) may decrease adipose tissue inflammation, thereby ameliorating such disturbances, even in the absence of fat loss. The purpose of this study was to 1) compare the effects of low-fat diet (LFD), EX, and their combination on inflammation, insulin resistance, and hepatic steatosis in high-fat diet-induced obese mice and 2) determine the effect of intervention duration (i.e., 6 vs. 12 wk). C57BL/6 mice (n ϭ 109) fed a 45% fat diet (HFD) for 6 wk were randomly assigned to an EX (treadmill: 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
156
1
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(181 citation statements)
references
References 37 publications
17
156
1
7
Order By: Relevance
“…35 Adipose tissue inflammation might also explain links between sedentary behaviour and inflammation. 36 Indeed, reductions in central adiposity largely explain the changes in CRP observed after aerobic exercise training interventions. 37,38 Thus, excess TV viewing may simply be a marker of chronic energy imbalance indicated by excess adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…35 Adipose tissue inflammation might also explain links between sedentary behaviour and inflammation. 36 Indeed, reductions in central adiposity largely explain the changes in CRP observed after aerobic exercise training interventions. 37,38 Thus, excess TV viewing may simply be a marker of chronic energy imbalance indicated by excess adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it was suggested that exercise intervention was more effective than low fat diet treatment for reducing hepatic steatosis, but both exercise and a low fat diet were effective in improving the anti-inflammatory response and metabolic outcomes [26,27].…”
Section: Introduction *mentioning
confidence: 99%
“…This leads to the stimulation of angiogenesis in adipose tissue and generally results in excessive adipose tissue growth and development with obesity being the eventual outcome. We have shown previously that both exercise and low fat diet reduce leptin gene expression in adipose tissue (52). This is relevant as leptin is also a target gene for HIF-1 (50).…”
Section: Future Directionsmentioning
confidence: 83%
“…Tissues were harvested immediately after sacrifice, weighed, flash frozen and stored for later analysis. This paradigm, with the exception of the added control group, is similar to the model used in a recently published study by our lab and summarized in figure 2 (52). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation